Italian women writers IWW ; bio-bibliographical information and a growing selection of full-text titles from authors born before 1945 (University of Chicago Library, 2002)
The Italian Women Writers project (IWW) is a long-term research endeavor to preserve and provide access to an extensive corpus of literature written by Italian women authors. IWW includes authors from the beginning of Italian literature in the late 12th and 13th centuries up to authors born in 1945. The following types of works will be included: anthologies, articles and essays, autobiographies, biographies, children's literature, devotional works, dialogues, diaries, dramas, epics, hagiographies, histories and chronicles, interviews and conversations, letters, memoirs, novels, operas, poems, reviews, short stories, and travel literature.